2004
DOI: 10.1002/j.2162-6057.2004.tb01242.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining and Assessing Problem‐Solving Style: Design and Development of a New Tool

Abstract: VIEW: An Assessment of Problem Solving Style (Selby, Treffinger, & Isaksen, 2002) is a new instrument for assessing problem‐solving style, for use with individuals from ages 12 through adult. It measures three dimensions of style relating to creative problem solving and change management. In this article, we discuss the construction of the instrument, the initial evidence supporting the instrument's reliability and validity, and a very brief overview of the instrument's foundations. Our reliability data involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 5 publications
(5 reference statements)
1
44
1
1
Order By: Relevance
“…Finally, there were more women than men (78 vs. 29) in the study, but this result is characteristic of the community college population and many higher education institutions today. The significant gender differences found in this study are not consistent with prior VIEW results (Selby et al, 2004) and suggest that more research is needed to understand these differences.…”
Section: Discussion Of the Characteristics Of Participants In Relatiocontrasting
confidence: 99%
See 3 more Smart Citations
“…Finally, there were more women than men (78 vs. 29) in the study, but this result is characteristic of the community college population and many higher education institutions today. The significant gender differences found in this study are not consistent with prior VIEW results (Selby et al, 2004) and suggest that more research is needed to understand these differences.…”
Section: Discussion Of the Characteristics Of Participants In Relatiocontrasting
confidence: 99%
“…This outcome is supported by VIEW research which shows that among the more than 20,000 VIEW takers since its development, the scores of Orientation to Change, Manner of Processing, and Ways of Deciding are not significantly correlated (Selby et al, 2004). The internal consistency estimates for the three VIEW scores for this study also were similar to those reported in the VIEW literature.…”
Section: Discussion Of the Results Related To The Intercorrelations Asupporting
confidence: 85%
See 2 more Smart Citations
“…Our problem-solving style model (Selby, Treffinger, Isaksen & Lauer, 2004;Treffinger, Selby, Isaksen, & Crumel, 2007) and the accompanying assessment instrument (Selby, Treffinger, & Isaksen, 2007a,b) involve three independent dimensions, which are: Orientation to Change (OC), with two general styles: the Explorer and the Developer; Manner of Processing (MP), with two styles: External and Internal; and, Ways of Deciding (WD), in which we define two styles: Person-focused and Taskfocused. Each dimension influences directly the ways people perceive problems and information, process data, generate possible solutions, make choices and decisions, and prepare to implement solutions.…”
Section: The Three Dimensions Of Problem-solving Stylementioning
confidence: 99%